2020
DOI: 10.1063/5.0033664
|View full text |Cite
|
Sign up to set email alerts
|

Numerically “exact” simulations of entropy production in the fully quantum regime: Boltzmann entropy vs von Neumann entropy

Abstract: We present a scheme to evaluate thermodynamic variables for a system coupled to a heat bath under a time-dependent external force using the quasi-static Helmholtz energy from the numerically "exact" hierarchical equations of motion (HEOM). We computed the entropy produced by a spin system strongly coupled to a non-Markovian heat bath for various temperatures. We showed that when changes to the external perturbation occurred sufficiently slowly, the system always reached thermal equilibrium. Thus, we calculated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 87 publications
1
32
0
Order By: Relevance
“…In terms of the vectors, |Φ(t) = e Λut |Φ and |Ψ(t) = e Λ † l t |Φ , we derive the modified HSEOM, in which the computation time is linear with t, as Eqs. ( 6) and (7). Figure 12 displays the real part of the three-body correlation function D 777 (t, 10) for (a) a TLS + spin lattice + QT ( /ω 0 = 1, ζ = 0.01, β ω 0 → ∞, blue), (b) a TLS + spin lattice ( /ω 0 = 1, ζ = 0, red), and (c) an isolated spin lattice ( /ω 0 = 0, ζ = 0, green).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the vectors, |Φ(t) = e Λut |Φ and |Ψ(t) = e Λ † l t |Φ , we derive the modified HSEOM, in which the computation time is linear with t, as Eqs. ( 6) and (7). Figure 12 displays the real part of the three-body correlation function D 777 (t, 10) for (a) a TLS + spin lattice + QT ( /ω 0 = 1, ζ = 0.01, β ω 0 → ∞, blue), (b) a TLS + spin lattice ( /ω 0 = 1, ζ = 0, red), and (c) an isolated spin lattice ( /ω 0 = 0, ζ = 0, green).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The heat bath is considered to be an unlimited heat source with infinite heat capacity. 7,8 However, the thermal noise from complex or frustrated materials is typically non-Gaussian, and its temporal and spatial correlations are non-uniform, although the ensemble average of the noise has a Gaussian profile when the strength of each source of noise is comparable, due to the central limit theorem. 9 The noise correlation is characterized by a simple function, for example, a stretched exponential function.…”
Section: Introductionmentioning
confidence: 99%
“…The distinctive feature of the HEOM approach is that it can rigorously evaluate changes in heat and entropy not only for the system but also for the bath and the SB interaction (117). We thus showed that quantum thermodynamics can be described in the framework of statistical mechanics, even in the nonequilibrium case, by regarding nonequilibrium work as a change in quasi-static free energy (131,133).…”
Section: Quantum Statistical Thermodynamicsmentioning
confidence: 93%
“…These equations could be of interest for exploring quantum thermodynamics in the case of strong system–bath coupling. 77 …”
Section: Coordinate Bathmentioning
confidence: 99%